Norwegian Nurses’ Attitudes Toward Assisted Dying: A Cross-Sectional Study - Hol H; Vatne S; Orøy A; Rokstad AMM; Opdal Ø (Dove Medical Press, 2022)
Hege Hol,1 Solfrid Vatne,1 Aud Orøy,1 Anne Marie Mork Rokstad,1,2 Øivind Opdal3 1Faculty of Health Science and Social Care, Molde University College, Molde, Norway; 2Norwegian National Centre for Ageing and Health, Vestfold Hospital Trust, Tønsberg, Norway; 3Faculty of Business Administration and Social Sciences, Molde University College, Molde, NorwayCorrespondence: Hege Hol, Faculty of Health Science and Social Care, Molde University College, Molde, Norway, Email hege.hol@himolde.noPurpose: The purpose was to investigate: (a) Norwegian nurses' attitudes toward assisted dying, and (b) how much nurses receive requests from terminally ill patients for help in dying.Participants and Methods: A quantitative explorative study was conducted using a web-based cross-sectional survey to collect data. The survey was sent to a total of 734 eligible participants, and 205 clinical nurses participated by completing the survey. Data were analyzed using bivariate statistics and multivariate ordinal regression.Results: The study revealed that 56% of the participating nurses agreed with the statement that physician-assisted suicide should be allowed, and 48% supported legalization of euthanasia. Nurses in pulmonary wards were more positive about the legalization of physician-assisted suicide (OR = 2.98, CI = 1.34- 6.66, p = 0.008) and euthanasia (OR = 3.51, CI = 1.58- 7.81, p = 0.002) than nurses in oncological wards. Nurses over 30 years old held more negative attitudes about physician-assisted suicide than younger nurses (OR = 0.16, CI = 0.07- 0.39, p < 0.001; and OR = 0.45, CI = 0.21- 0.96, p = 0.038), and nurses with postgraduate education held more negative attitudes than nurses with a bachelor's degree (OR = 0.46, CI = 0.24- 0.88, p = 0.019). A total of 118 nurses (58%) had received at least one request about assisted dying in their clinical practice.Conclusion: Our results provide insight into clinical nurses' attitudes toward assisted dying. Their attitudes were influenced by their age, education, and practice in different wards. Support for legalization of assisted dying is higher in the general Norwegian population than among nurses and receiving requests for assisted dying is not unusual for clinical nurses.Keywords: euthanasia, physician-assisted suicide, nursing, web-based survey